Research of the properties of protein hydrolysates obtained from the broiler chicken gizzards as a potential component of bioactive film coatings - O. V. Zinina; S. P. Merenkova; M. B. Rebezov; E. A. Vishnyakova (Пищевые системы)
Protein hydrolysates are a promising active component in the production of bioactive film coatings for food products. Some biopolymers can exert the biological activity. More often, however, it is necessary to select biologically active substances to impart these properties to films. On the other hand, not all components allow forming films with the required properties, and therefore there is a need to study the individual technological characteristics of the components used. The purpose of the research is to establish the antioxidant and technological properties of protein hydrolysates obtained by microbial fermentation of poultry by-products in whey with bifidobacteria, propionic acid bacteria and acidophilic bacteria as a potential basis for bioactive film coatings of food products. The hydrolysate obtained by fermentation without the addition of the specified bacterial species was used as a control sample. The functional properties of protein hydrolysates were assessed: antioxidant capacity by coulometric titration on an Expert-006 coulometer using ascorbic acid as a standard, antiradical activity by the DPPH method on a Jenway 6405 UV/Vis spectrophotometer with determination of the IC50 value. The technological properties, solubility, water-holding, fat-holding and fat-emulsifying capacities were also determined by the gravimetric method. In addition, the average hydrodynamic diameter of particles in protein hydrolysates was determined using a Microtrac FLEX particle size analyzer. The results of studies of the antioxidant properties showed that the DPPH antiradical activity was 14.7% higher in the experimental samples of hydrolysates obtained by fermentation with bifidobacteria compared to the control; samples of hydrolysates obtained by fermentation with propionic acid bacteria showed an antioxidant capacity 29.6% higher than that of the control sample. The IC50 value turned out to be the highest in the control hydrolysate sample (2.994 mg/ml), which was 45.5–53.3% higher than that in the experimental hydrolysate samples. The results of determining the technological properties showed that they differ significantly for protein hydrolysates obtained by fermentation with different types of bacteria. For example, the highest values of fat-holding and fat-emulsifying capacities were found in the hydrolysate obtained by fermentation with bifidobacteria (351.1% and 61%, respectively), which shows its potential for incorporation into the bio-composite in the form of a protein-oil emulsion. The high solubility of the experimental samples of hydrolysates (from 90.1 to 91.4%) suggests their uniform distribution in the aqueous phase when composing the biocomposite of the film. Thus, the research results have shown the prospects of using protein hydrolysates from the gizzards of broiler chickens in whey as an active component of bioactive film coatings. The antioxidant properties of protein hydrolysates allow slowing down oxidative processes in the main food nutrients, which will contribute to an increase in the shelf life of food products packaged in bioac- tive films with this component.